Relationship between laser energy input, microstructures and magnetic properties of selective laser melted Fe-6.9%wt Si soft magnets - Garibaldi, M.; Ashcroft, I.; Hillier, N.; Harmon, S.A.C.; Hague, R. (Materials characterization, 2018)
Selective Laser Melting (SLM), a powder-bed Additive Manufacturing technology, can be used in combination with high temperature post-annealing to produce high-silicon steel parts characterised by quasi-static magnetic properties comparable to those of commercial electrical steel. However, the role of the as-built microstructure on the magnetic properties is still unexplored. Therefore, in this study the effect of the energy input of the processing laser on the magnetic properties of the material is investigated. The magnetic properties are determined for 4 mm-high rings obtained using three laser energy input values that provide a good compromise in terms of porosity and crack formation. The best magnetic properties are obtained for the rings built using a value of energy input that produces a strong fibrous crystallographic texture, in which one of the crystallographic 〈001〉 axes is preferentially aligned along the build direction. Whether the magnetic properties change with sample direction as a result of the crystallographic texture will be the subject of future research. [Display omitted] •Effect of laser energy input on magnetic properties of SLM Fe-6.9%wt.Si is described;•Magnetic properties can be described as function of as-built microstructure after stress-relief post-treatment;•Samples with density >99% and strong crystallographic texture along BD have the best magnetic properties;•At very high laser energy, a strong cube texture forms that deteriorates the magnetic properties.